Café dan Identitas Sosial Generasi Milineal di Surabaya (Jurnal ENTITAS SOSIOLOGI, 2022)
This study examines the selection of cafes by the Surabaya millenniasl from a sociological point of view. Hanging out in a café is a lifestyle for the millennials and it reflects their social identity. This study aims to describe their choice over a cafe in Surabaya and how they form their social identity through the selection. The research method used is a qualitative method with a descriptive approach. This research was conducted in lower, middle and upper class cafes in Surabaya. The data collection technique used is non-participant observation and interviews with six informants. The results show that the backgrounds of the millennials in the selection of cafes in Surabaya are its unique atmosphere, cleanlines, cool air, fame, close distance from home. The atmosphere is the most important factor in choosing the cafe because it shapes the social identity of the millennials of Surabaya. They show their social identity through social media and their appearance. The millennial generation forms a social identity according to the image they want to show to others; to look populist, cool, successful and trustworthy.